The Early Secretory Pathway Is Crucial for Multiple Aspects of the Hepatitis C Virus Life Cycle - Avula, Kiran; Singh, Bharati; Samantaray, Subhashish; Syed, Gulam Hussain (Journal of virology, 2023)
The virus life cycle involves entry into the host, replication of the genome, assembly of infectious progeny, and their subsequent release. Different aspects of the HCV life cycle, including entry, genome replication, and assembly, are well characterized; however, our understanding of the HCV release is still not clear and subject to debate due to varied findings. Although most of the early events of the hepatitis C virus (HCV) life cycle are well characterized, our understanding of HCV egress is still unclear. Some reports implicate the conventional endoplasmic reticulum (ER)-Golgi route, while some propose noncanonical secretory routes. Initially, the envelopment of HCV nucleocapsid occurs by budding into the ER lumen. Subsequently, the HCV particle exit from the ER is assumed to be mediated by coat protein complex II (COPII) vesicles. COPII vesicle biogenesis also involves the recruitment of cargo to the site of vesicle biogenesis via interaction with COPII inner coat proteins. We investigated the modulation and the specific role of the individual components of the early secretory pathway in HCV egress. We observed that HCV inhibits cellular protein secretion and triggers the reorganization of the ER exit sites and ER-Golgi intermediate compartments (ERGIC). Gene-specific knockdown of the components of this pathway such as SEC16A, TFG, ERGIC-53, and COPII coat proteins demonstrated the functional significance of these components and the distinct role played by these proteins in various aspects of the HCV life cycle. SEC16A is essential for multiple steps in the HCV life cycle, whereas TFG is specifically involved in HCV egress and ERGIC-53 is crucial for HCV entry. Overall, our study establishes that the components of the early secretory pathway are essential for HCV propagation and emphasize the importance of the ER-Golgi secretory route in this process. Surprisingly, these components are also required for the early stages of the HCV life cycle due to their role in overall intracellular trafficking and homeostasis of the cellular endomembrane system. IMPORTANCE The virus life cycle involves entry into the host, replication of the genome, assembly of infectious progeny, and their subsequent release. Different aspects of the HCV life cycle, including entry, genome replication, and assembly, are well characterized; however, our understanding of the HCV release is still not clear and subject to debate due to varied findings. Here, we attempted to address this controversy and enhance our understanding of HCV egress by evaluating the role of the different components of the early secretory pathway in the HCV life cycle. To our surprise, we found that the components of the early secretory pathway are not only essential for HCV release but also contribute to many other earlier events of the HCV life cycle. This study emphasizes the importance of the early secretory pathway for the establishment of productive HCV infection in hepatocytes.